2005
DOI: 10.1080/00365510510013659
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of aquaporin‐2 after furosemide and felodipine in healthy humans

Abstract: Furosemide treatment increased U-AQP2, AVP, and the activity of the renin-angiotensin-aldosterone system. These changes are most likely compensatory phenomena, which prevent an excess loss of sodium and water. Felodipine tended to increase U-AQP2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
5
14
1
Order By: Relevance
“…In the present study, cardiac function was improved in CHF rats treated with Sclederma of Poria cocos (hoelen), with a slight reduction of plasma AVP and renal V2R-AQP2. In contrast, there is no change in plasma BNP levels with the enhancement of AVP-V2R-AQP2 in CHF rats treated with furosemide, which is consistent with previous studies (Starklint et al, 2005(Starklint et al, , 2006. This suggests that Sclederma of Poria cocos (hoelen) may exert its diuretic effect and improve cardiac function by reducing AVP-V2R-AQP2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, cardiac function was improved in CHF rats treated with Sclederma of Poria cocos (hoelen), with a slight reduction of plasma AVP and renal V2R-AQP2. In contrast, there is no change in plasma BNP levels with the enhancement of AVP-V2R-AQP2 in CHF rats treated with furosemide, which is consistent with previous studies (Starklint et al, 2005(Starklint et al, , 2006. This suggests that Sclederma of Poria cocos (hoelen) may exert its diuretic effect and improve cardiac function by reducing AVP-V2R-AQP2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…In the majority of studies, GFR increased (5,13,14,71,120,121,133,169) or remained stable (31,42,102,147); in five studies GFR decreased (51,91,100,158). RBF increased in five (71,102,115,121,169), remained stable in three (42,51,120), decreased in one (51), and was not reported in the other studies (5, 13, 14, 31, 91, 100, 133, 147, 158).…”
Section: Questions Regarding Hemodynamics and Vascular Regulation Andmentioning
confidence: 77%
“…Furosemide has been associated with worsening of kidney function in patients treated for volume overload admitted for acute heart failure (104) and even glomerular filtration rate (GFR) responses to furosemide in healthy subjects are variable (5,13,14,31,42,51,71,91,100,102,115,120,121,133,147,158,169). The very strong and short actions of furosemide have been associated with rebound sodium retention, and it has been brought to question whether furosemide would allow the reaching of a new steady state.…”
mentioning
confidence: 99%
“…Second, all patients in this study were free of treatment (specifically diuretic drugs) known to alter the abundance of aquaporin protein in the kidneys and therefore in urine. [25][26][27] Indeed, increased excretion of urinary aquaporin-2 has been demonstrated during furosemide treatment. 27 In the Pedersen study, 9 of 14 patients with cirrhosis received diuretics up to 24 hours prior to urine collection, and in the Ivarsen study all patients were receiving diuretic treatment at the time of urine collection.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Indeed, increased excretion of urinary aquaporin-2 has been demonstrated during furosemide treatment. 27 In the Pedersen study, 9 of 14 patients with cirrhosis received diuretics up to 24 hours prior to urine collection, and in the Ivarsen study all patients were receiving diuretic treatment at the time of urine collection. Finally, although the technique used to detect urine aquaporin-2 differed among the 3 studies-dot-blot analysis in the Ivarsen study, radioimmunoassay in the Pedersen study, and immunoblot in our study-we do not think this can explain the differences found in aquaporin-2 urinary excretion.…”
Section: Discussionmentioning
confidence: 99%